POLA ASUH ORANGTUA DEMOKRATIS, KREATIVITAS DAN ADVERSITY QUOTIENT REMAJA AWAL - Iswantiningtyas, Veny (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract, Relationship of democratic parenting, creativity and Adversity Quotient examined on 101 boys and 131 girls, 13 to 16 years of ages, and living with biologic parents. Data obtained from the scales of C.O.R.E, CO2RE and â€œPâ€ and analyzed with regression. Democratic parenting are highly significant predict creativity; Democratic parenting are highly significant predict Adversity Quotient total scores; No relationship between democratic parenting with sub scales of Control and Endurance; Positive relationship and significant between democratic parenting with sub scales of Origin, Ownership and Reach. The findings are discussed in terms of their implications for middle adolescent in context.Â Keywords: democratic parenting, creativity, adversity quotient